Reoccurrence of takotsubo cardiomyopathy induced by osimertinib: A case report. Issue 9 (2nd September 2022) - Fukuda, Yuko; Kawa, Yoshitaka; Nonaka, Akiko; Shiotani, Hideyuki
Abstract : A patient with lung cancer was administrated osimertinib. She developed symptomatic heart failure due to Takotsubo cardiomyopathy (TC). As her condition improved after discontinuing osimertinib, TC was thought to be caused by osimertinib. Reoccurrence of TC was seen after readministrating half dose of osimertinib.